The Application of Snakes and Ladders Game in Teaching Vocabulary - . Meipina (International Conference on Education and Language (ICEL), 2014)
The objectives of this research were aimed to determine the best technique which could be used to teach vocabulary with snakes and ladders at grade seven of SMPN 20 Bandar Lampung, to investigate how the game was applied in learning process, to analyzed problems in the application of the game, and to identify advantages in the use of the game. Data were collected by three way, first way was observation involved three stages, namely a pre-test, teaching treatment, and a post-test. The second way was questionnaire. The third way was interview. Data were collected through observation, interview, and student’s questionnaire. The writer started by analyzing data from the observation using the video of recording which had been recorded. The writer analyzed students Questionnaire from the question one until ten. The last the writer analyzed data from students interview.The results were driven from observation, interview and questionnaire. The observation investigated the use of snakes and ladders in vocabulary teaching and determined the best technique for the game. The interview analyzed problems in learning process. The questionnaire identified advantages in the use of game.